2016
DOI: 10.1016/j.jcat.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

One step-synthesis of highly dispersed iron species into silica for propylene epoxidation with dioxygen

Abstract: Well dispersed iron catalysts were synthesized in silica (Fe 0.0X SiO 2 ) by a one-step synthesis procedure. These materials were tested in the propylene epoxidation reaction with gaseous O 2 . The influence of the iron metal loading on the iron incorporation and distribution in the support (both influenced by the synthetic procedure) were thoroughly studied (conversion, generation and selectivity). Electron Microscopy and UltraViolet-Visible (UV-VIS), Raman and Fourier Transform Infrared Spectroscopy (FTIR) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Generally, low nuclearity species reduces at high temperature due to strong interaction with the support, while the reverse is likely for the high nuclearity species. The first reduction peak centered at 410 °C is attributed to two‐dimensional oligomeric FeO x species as there is no evidence for three dimensional Fe 2 O 3 crystallites in DRS‐UV and EPR results . It has been reported in the literature that reduction of single site iron takes place between 600 °C to 700 °C.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Generally, low nuclearity species reduces at high temperature due to strong interaction with the support, while the reverse is likely for the high nuclearity species. The first reduction peak centered at 410 °C is attributed to two‐dimensional oligomeric FeO x species as there is no evidence for three dimensional Fe 2 O 3 crystallites in DRS‐UV and EPR results . It has been reported in the literature that reduction of single site iron takes place between 600 °C to 700 °C.…”
Section: Resultsmentioning
confidence: 84%
“…DRS‐UV spectrum of 8 wt %Fe/SBA‐15 (Supporting Information, Figure S5) showed a weak signal at 220 nm and a peak at 250 nm due to oxygen to Fe III charge transfer involving isolated Fe III in octahedral environment . Furthermore, an intense band at 330 nm and a shoulder at 470 nm at higher wavelength can be assigned to Fe III ‐clusters and amorphous FeO x oligomers, respectively, due to increase in the nuclearity of Fe III oxide ,,. The absence of peak beyond 500 nm undoubtedly indicates the absence of bulk iron oxide phase formation in the mesopores during the grafting process …”
Section: Resultsmentioning
confidence: 99%
“…Despite this, a limited number of sources has explored other routes, such as the formation of an hydroperoxo-Fe(porphyrin) complexes in P45models [55][56][57][58][59], in non-porphyrinic Fe catalysts [60][61][62][63] and also on Mn catalysts [64][65][66][67]. Nevertheless, the activity of such hydroperoxo species towards epoxidation reactions has been questioned by Shaik and co-workers [68], at least in models of cytochrome P450.…”
Section: Insights On the Reaction Mechanismmentioning
confidence: 99%
“…But the result of direct epoxidation of propylene catalyzed by Fe x SiO 2 or Sb 2 O 3 –CuO–NaCl/SiO 2 without other auxiliaries is still unsatisfactory , . Base‐metal complex, like Manganese(III) or Nickel(II) complexes used as catalyst in the olefins epoxidation had been investigated by T. Yamada et al,, it revealed that the co‐reductant aldehyde was necessary and did have a significant influence on the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%